Formal Issues in Austronesian Linguistics
XI, 265 p.
Keywords: Austronesian languages have long raised interesting questions for generative theories of syntax and morphology. The papers in this volume encompass some of these traditional questions and place them in newer theoretical contexts. Some of the papers also address new issues which add to our understanding of members of this language family on one side and the nature of linguistic theories on the other. There are three broad issues that re-occur throughout the volume - the role and analysis of verbal morphology, the nature of the subject or the topic in these languages, and the interaction of syntax and specificity. The papers in this volume show that as formal theories become more precise, a wider range of language data can be captured, and as the inventory of language data grows, the accuracy of formal linguistic theories improves.